Pengembangan Inventori Perkembangan Siswa (IPS) - Kasmayani Anwar; Abdul Saman (Program Studi bimbingan Konseling PPs UNM Makassar, 2018)
The study aims to find out (1) an overview of the needs analysis for the use of Student Development Inventories (IPS). (2) How is the prototype for developing student development inventory (IPS), (3) the level of validity, reliability and feasibility of developing a Student Development Inventory (IPS) as one of the data collection tools in State High School 9 Bulukumba. Research is a research or development research involving 15 high school students in a small group trial. The results showed (1) Student development inventory (IPS) as a measuring instrument / instrument is very needed, in the form of updates or updates in terms of form, content and problem areas of BK and too many statement items that make students tired of reading and filling inventory. (2) Prototype Student development inventory (IPS) developed in full with manuals, so that guidance and counseling teachers can use inventory. (3) the results of the trial obtained the value of student development inventory validity (IPS) are on a scale of 4.17 at the stage of validity expert test with valid criteria, the value of reliability test obtained high criteria or reliable, so it can be concluded that student development inventory (IPS) with a number of 76 items that are valid, reliable statements can be used as student development inventories (IPS)